1991
DOI: 10.1172/jci115492
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of fetal fibronectin mRNAs during the development of rat cardiac hypertrophy induced by pressure overload.

Abstract: Cardiac pressure overload induces a shift towards the fetal form of major proteins expressed by the myocytes, and an accumulation of extracellular matrix proteins. One of them, fibronectin (FN), accumulates soon after the imposition of pressure overload. Because FN exists both as cellular FN (c-FN) locally synthesized by nonmuscle cells and as "plasma-FN" (p-FN) synthesized by the hepatocytes, the first issue of this study was to determine whether FN accumulation within the myocardium in response to pressure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(38 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…The histochemical data shown in this study indicate that the observed increase in immunodetectable fibronectin was also localized in the fibrotic regions. We (4) and others (22) had previously used in situ hybridization to localize these changes to regions of fibroblast proliferation and showed that fibronectin expression increased before changes in collagen expression, a finding consistent with other models of wound healing. The amount of ang II we used to produce extensive cardiac fibrosis in the L-NAME-treated rats was insufficient to cause similar changes in rats not given L-NAME, suggesting a synergistic effect between L-NAME and ang II on the development of cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 79%
“…The histochemical data shown in this study indicate that the observed increase in immunodetectable fibronectin was also localized in the fibrotic regions. We (4) and others (22) had previously used in situ hybridization to localize these changes to regions of fibroblast proliferation and showed that fibronectin expression increased before changes in collagen expression, a finding consistent with other models of wound healing. The amount of ang II we used to produce extensive cardiac fibrosis in the L-NAME-treated rats was insufficient to cause similar changes in rats not given L-NAME, suggesting a synergistic effect between L-NAME and ang II on the development of cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 79%
“…For each transcript, the differential expression is given as the T/N ratio. * P Ͻ 0.05. fetal form, as already described during pressure overload (47,45). Fibronectin was identified using relative RT-PCR analysis with primers located within part of the 3Ј-UTR.…”
Section: Discussionmentioning
confidence: 80%
“…The enhanced expression of a ubiquitous SERCA 2 isoform can be related to a shift toward more immature phenotype of smooth muscle cells as previously suggested. 46 The change in SERCA 2b expression in vessels, however, was not associated with an alteration in IP 3 R mRNA level.…”
Section: Discussionmentioning
confidence: 88%